Quantification of the Fracture Complexity of Shale Cores After Triaxial Fracturing - Zhang, Yonghao; Ma, Jinfeng; Wang, Yang; Wang, Fei; Li, Xin; Zhao, Luanxiao (Frontiers in Earth Science, 2022)
Diagnosing fractures under compression is of great importance in optimizing hydraulic fracturing stimulation strategies for unconventional reservoirs. However, a lot of information, such as fracture morphology and fracture complexity, is far from being fully excavated in the laboratory limited by the immature fracture identification techniques. In the current study, we propose a set of methods to analyze the fracture complexity of cylindrical cores after triaxial fracturing. Rock failure under conventional compression tests is real-time controlled by monitoring the stress-strain evolutions to ensure that the cores remain cylindrical after failure. The lateral surface of the core cylinders is scanned with a 2D optical scanner to extract the fracture parameters, the surface fracture rate and the inclination dispersion, which are normalized and averaged to derive the fracture complexity. After analyzing the data for 24 shale gas reservoir cores from the Sichuan Basin, the fractal dimension of fracture images shows a good linear correlation with the surface fracture rate, but has no correlation with the dip dispersion. The calculated fracture complexity nearly has no relationship with the E-ν-based brittleness index, but demonstrates a positive correlation with the mineral-content-based brittleness index. Moreover, the fracture complexity is associated with the core mineralogical compositions. The fracture complexity is positively correlated with the content of quartz, calcite and dolomite, is negatively correlated with the content of clay minerals, and has no obvious relationship with the content of feldspar. The proposed method provides an experimental basis for the evaluation of fracturability of unconventional oil and gas reservoirs.